2020
DOI: 10.1371/journal.pone.0234146
|View full text |Cite
|
Sign up to set email alerts
|

Loss of STAT6 leads to anchorage-independent growth and trastuzumab resistance in HER2+ breast cancer cells

Abstract: Approximately 20% of breast cancers are HER2-positive. Trastuzumab has improved patient outcomes significantly for these cancers. However, acquired resistance remains a major hurdle in the clinical management of these patients. Therefore, identifying molecular changes that cause trastuzumab resistance is worthwhile. STAT6 is a transcription factor that regulates a variety of genes involved in cell cycle regulation, growth inhibition, and apoptosis. STAT6 expression is lost in approximately 3% of breast cancers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Here, and in keeping with reported functions for SOCS proteins as suppressors of JAK/STAT pathways, we did find that SOCS5 (and LINC01119) inhibited the phosphoactivation of STAT6, but not the traditional targets STAT1 or STAT3. Of pertinence, STAT6 has been described to act as a tumor suppressor in breast cancer 69,70 , providing a possible mechanism-of-action of LINC01119/SOCS5 in driving TNBC cell growth by curtailing STAT6 activation. In support of this notion are genetic data demonstrating STAT6 negative correlation with both LINC01119 and SOCS5 in patient cohorts, and the fact that STAT6 downregulation was itself associated with TNBC and forecasted poor TNBC patient prognosis (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Here, and in keeping with reported functions for SOCS proteins as suppressors of JAK/STAT pathways, we did find that SOCS5 (and LINC01119) inhibited the phosphoactivation of STAT6, but not the traditional targets STAT1 or STAT3. Of pertinence, STAT6 has been described to act as a tumor suppressor in breast cancer 69,70 , providing a possible mechanism-of-action of LINC01119/SOCS5 in driving TNBC cell growth by curtailing STAT6 activation. In support of this notion are genetic data demonstrating STAT6 negative correlation with both LINC01119 and SOCS5 in patient cohorts, and the fact that STAT6 downregulation was itself associated with TNBC and forecasted poor TNBC patient prognosis (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…STAT6 acts as an important TF that takes part in the cell cycle, cell growth, and apoptosis. DiScala et al (2020 ) found that loss of STAT6 results in trastuzumab resistance in HER2+ breast cancer cells. IRF1 functions in immune response, DNA damage, and DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the relationship between HER2 overexpression and sensitivity to PARPi, we used lentivirus-mediate HER2 overexpression to create an isogenic panel of MCF-10A human breast epithelial cells, referred to as MCF-10A-HER2. Isogenic MCF-10A-HER2 cell lines were generated as previously described [22]. The resulting clones, exhibited EGFindependent growth, a surrogate marker of cell transformation in MCF-10A cells, indicating that cell growth is driven through HER2 receptor signaling [23].…”
Section: Her2 Overexpressing Mcf10a Cells Are Sensitive To Olaparibmentioning
confidence: 99%